Chemical constituents and biological activities of two rutaceous plants : Clausena excavata Burm. and Evodia malayana Ridl. - Oktima, Winda (2013)
Phytochemical and biological activity studies on two Sumatran Rutaceae plants were carried out. Both Clausena excavata Burm. and Evodia malayana Ridl., were subjected to detail isolation work. The plants were extracted by using three organic solvents of different polarity, followed by isolation of the compounds by using several common chromatography techniques, such as gravity column chromatography, vacuum flash chromatography, radial chromatography and preparative thin layer chromatography. The structural elucidations of isolated compound were carried out by using various spectroscopic techniques including infrared (IR), mass spectroscopy (MS), nuclear magnetic resonance (NMR) and also by comparison with literature data. The phytochemical investigations have led to the isolation of several compounds of different classes, including coumarins, alkaloid, flavonoid, lignan, acridin derivative and phytosterols. The crude extracts and some of the isolated compounds were screened for antimicrobial, antioxidant and cytotoxic activities, using disc diffusion method, DPPH (1,1-diphenyl-2-picrylhydrazyl) and MTT (Microculture Tetrazolium Salt) assay, respectively. The antimicrobial activity was tested against nine selected bacteria named Bacillus cereus, Bacillus subtilis, Escherichia coli, Enterobachter aerogenes, Klebsiella pneumonia, Salmonella typhimurium, Staphylococcus aureus, Aspergillus niger and Candida albicans, respectively. The cell line used in cytotoxic assay was MCF-7, the human adenocarcinoma breast cancer cell line. The phytochemical study on Clausena excavata Burm. has led to the isolation of four coumarins, seselin (141), imperatorin (65), xanthyletin (37), xantotoxol (142), an alkaloid, murrayanin (143) and β-sitosterol (140). From the isolation work on Evodia malayana Burm. has yielded a lignan, sesamin (145), a flavonoid, pachypodol (146), an acridin derivative, 1,3-dimethoxy-10H-acridin-9-one (147) together with two phytosterols β-sitosterol (140) and stigmasterol (144). This acridin derivative was firstly reported to be isolated from natural origin and also new constituent to E. malayana Ridl. Among the isolated compounds, imperatorin (65) and xanthotoxol (37) exhibited the moderate activity toward Escherichia coli, Enterobachter aerogenes and Staphylococcus aureus. In cytotoxic study, seselin (141), xanthotoxol (142) and sesamin (145) displayed remarkable potential activity against MCF-7 cell line, while potential radical scavenging activity was shown by xanthotoxol (142). Xanthotoxol (142) showed the excellent activities in all assays which have been conducted in this study, and becomes a strong reason for further drug discovery study.